The Effect of Prior Learning on Table Tennis Instruction in Young Women with Disabilities in Tehran - Jalilbal , Zeynab; Taghiyar , Pegah; Soltani , Mahsa; Hasanlo, Sahar (Health Nexus, 2025)
The present study was conducted to examine the effect of prior learning on table tennis instruction in young women with disabilities in the city of Tehran. This research employed a quasi-experimental method with a pretest-posttest design including experimental and control groups. The statistical population consisted of female athletes with physical disabilities from Hazrat Abolfazl Sports Club in District 15 of Tehran in the year 2022. The research sample included 20 participants who were divided into two groups of 10 (experimental and control) using a group homogenization method. The research instrument was a researcher-made checklist on table tennis techniques. Data analysis was conducted using multivariate analysis of covariance (MANCOVA). The findings indicated that there was a statistically significant difference in the scores for forehand push serve, backhand push serve, forehand chop, and backhand chop. A significant difference was observed at the 0.01 error level in the posttest stage between the experimental and control groups. It can be concluded that the prior learning intervention was effective in improving table tennis instruction for young women with disabilities in Tehran.